Doing things with description: practices, politics, and the art of attentiveness. (June 2021) - Vitellone, Nicole; Mair, Michael; Kierans, Ciara
In a number of linked articles and monographs over the last decade (e.g. Love, 2010, 2013, 2015, 2016, 2017), literary scholar and critic Heather Love has called for a descriptive (re)turn in the humanities, repeatedly taking up examples of descriptive methods in the social sciences as exemplifying what that (re)turn might look like and achieve. Those of us working as sociologists, anthropologists, science and technology studies scholars and researchers in allied social science fields thus find ourselves reflected back in Love's work, encountering our own research practices in an unfamiliar light through it. In a period where our established methods and analytical priorities are subject to challenges on many fronts from within our own disciplines, it is hard not be struck by Love's provocative invocation of the social sciences as interlocutors and see in it an invitation to contribute to the debate she has sought to initiate by revisiting our own approaches to the problem of description. Inspired by Love's intervention, the eight papers that form this Special Issue demonstrate that by re-engaging with description we stand to learn a great deal. While the articles themselves are topically distinct and geographically varied, they are all based on empirical research and written to facilitate a reorientation to the role of description in our research practices. What exactly is going on when we describe an ancient papyrus as present or missing, a machine as intelligent, noise as music, a disease as undiagnosable, a death as good or bad, deserved or undeserved, care as appropriate or inappropriate, policies as failing or effective? As the papers show, these are important questions to ask. By asking them, we find ourselves in positions to better understand what goes into 'indexing and making visible forms of material and social reality' (Love, 2013: 412) as well as what is involved, more troublingly, in erasing, making invisible and dematerialising those realities or even, indeed, in uncovering those erasures and the means by which they were effected. As this special issue underlines, thinking with Love by thinking with descriptions is a rewarding exercise precisely because it opens these matters up to view. We hope others take up Love's invitation to re-engage with description for that very reason.